Implementasi Pendidikan Karakter Kepada Peserta Didik di TKIT Al Fatah - Iis Dewi Lestari (Universitas Indraprasta PGRI Jakarta, 2022)
Kindergarten students in golden age are very important to develop their personality that have character values to produce bright generations in the future. The fading of the values of discipline, honesty, independence, lack of a sense of responsibility to students is certainly a problem found in schools. Because noadays, many students have faded in applying character values. The purpose of this study was to find out how the implementation of character education for students in kindergarten in Islamic-based education schools. The methodology of this research was descriptive qualitative. The object of this research was the implementation of character education while the research subjects were teachers and students at TKIT Al Fatah. Data analysis techniques were carried out by collecting data, reducing data, presenting data and drawing conclusions. Data collection techniques used are observation, interviews and documentation. This research was conducted from January to April 2022. The results of this study 1) the implementation of character education in TKIT Al Fatah ran by implementing activities inside and outside the classroom that contained character values for students, 2) TKIT AL Fatah implemented character values namely religious, independent, disciplined and responsible for producing a generation that has good morals, 3) teachers, parents and the community played a very important role in instilling character values to students.